1977
DOI: 10.1302/0301-620x.59b3.893517
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of osteochondritis dissecans. Failure to establish a familial background

Abstract: In a family study in which thirty-four patients with osteochondritis dissecans and eighty-six of their first-degree relatives were examined clinically and radiologically, only one relative was found to have osteochondritis dissecans. No association with other forms of osteochondritis, endocrinological abnormalities or dwarfism was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

1980
1980
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(31 citation statements)
references
References 0 publications
1
28
1
1
Order By: Relevance
“…In our situation, both twins presented with OCD of the left side and one twin presented with a bilateral occurrence. Our findings support those of Petrie [17], who also suggested genetics play a role in the formation of OCD. However, in that paper and our study, genetic causation could not be established.…”
Section: Discussionsupporting
confidence: 92%
“…In our situation, both twins presented with OCD of the left side and one twin presented with a bilateral occurrence. Our findings support those of Petrie [17], who also suggested genetics play a role in the formation of OCD. However, in that paper and our study, genetic causation could not be established.…”
Section: Discussionsupporting
confidence: 92%
“…An autosomal-dominant inheritance pattern is espoused by at least two separate authors [58,68]. However, disputing the evidence of familial inheritance, Petrie [67] reported on a radiographic examination of first-degree relatives and discovered only 1.2% with an OCD. Although genetics may still play a role, the association remains elusive.…”
Section: Etiologymentioning
confidence: 99%
“…Although Petrie first concluded that OCD does not have a familial association in 1977, multiple case reports have been published since then that demonstrate a potentially heritable genetic component to the etiology of OCD [20]. Specifically, many of these recent case reports have described OCD lesions in sets of monozygotic twins, including some in which the appearance of the lesions themselves is identical [5,9,15,17,19,21].…”
Section: Introductionmentioning
confidence: 99%